Respectful Culture as a Model for Gurèe Communication and Da’wah Implementation in Dayah Bireuen Regency - Azizi, Muhammad Abrar; Abdullah, Abdullah; Rubino, Rubino (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
This research aims to analyze the application of the gurèe communication model in building a culture of takzim for students in Bireuen Regency, Aceh Province. This research uses a qualitative method with a phenomenological approach. The data collection process was carried out using documentation study tools, observation, field notes, and interviews involving gurèe and dayah students who are involved in gurèe communication. This research involved three dayah in Bireuen Regency as research locations. The research results show that gurèe communication plays an important role in building a culture of respect among dayah students. The gurèe communication model involves a close relationship between the gurèe and the santri, who serve as role models and spiritual guides for the santri. The culture of takzim is the result of the application of the gurèe communication model among dayah students. This culture includes respect for the gurèe, politeness in speaking, humility, and obedience to religious rules and values. The implication of this research is that the gurèe communication model plays an important role in shaping the takzim culture among dayah students. Through communication filled with respect, politeness, and adherence to religious values, the messages conveyed by the gurèe can be well-received and implemented by the santri. This strengthens the bond between the gurèe and the santri and maintains the originality of the message that supports the creation of a sustainable culture of respect in Bireuen Regency.